Multiuser MISO Transmitter Optimization for Intercell Interference Mitigation - Hoon Huh; Papadopoulos, H C; Caire, G (IEEE transactions on signal processing, 2010)
The transmitter optimization (i.e., steering vectors and power allocation) for a MISO broadcast channel subject to general linear constraints is considered. Such constraints include, as special cases, the sum-power, per-antenna or per-group-of-antennas power, and "forbidden interference direction" constraints. We consider both the optimal dirty-paper coding and simple suboptimal linear zero-forcing beamforming strategies, and provide numerically efficient algorithms that solve the problem in its most general form. As an application, we consider a multicell scenario with partial cell cooperation, where each cell optimizes its transmitter by taking into account interference constraints on specific users in adjacent cells. The effectiveness of the proposed method is evaluated in a simple system scenario including two adjacent cells and distance-dependent pathloss, under different fairness criteria that emphasize the bottleneck effect of users near the cell "edge." Our results show that this "active" Intercell Interference (ICI) mitigation outperforms the conventional "static" ICI mitigation based on fractional frequency reuse.